Os tons do trágico em Ariano Suassuna: uma leitura de Uma mulher vestida de sol - Kersch, Teresinha de Oliveira Ledo (2012)
The main objective of this research is to apprehend the construction of The Tragic and the intentionality of a poetic voice that inscribes the reader s body on the text in the play Uma mulher vestida de sol, by Ariano Suassuna. We believe that this play is a kind of a Dionysian tragedy , which incorporates comic and popular elements, in order to intensify its performance. The play has three acts and tells the story of the love between two young people, Francisco and Rosa, both love each other but come from families who fight because of land pieces in the wilderness of Taperoá. We use Poética by Aristóteles as the theoretical basis and Paul Zumthor s theory on performance. The first one names and discusses the elements of Tragedy and the second one, the elements of voice in popular culture; we can read about the latter in books such as Performance, recepção e leitura and Escritura e nomadismo. Suassuna s work does not only dialogue with the canonical texts of the universal literature, but also with popular culture, with specific kinds of texts produced in Brazil such as cordel literature, folhetos, almanaques, rezas and cantorias (stories on strings, leaflets, almanacs, prayers and songs). We focus on the insertion of Suassuna s Theater in the Armorial Movement and we propose the search of oral sources using Zumthor s concept of movência (mouvance). The results of this research highlight that the intention in the play performance is expanded because of the oral elements brought by the popular culture